Molecular basis of acute cystitis reveals susceptibility genes and immunotherapeutic targets - Ambite, Ines; Miethke, Thomas (PLoS pathogens, 2016)
Tissue damage is usually regarded as a necessary price to pay for successful elimination of pathogens by the innate immune defense. Yet, it is possible to distinguish protective from destructive effects of innate immune activation and selectively attenuate molecular nodes that create pathology. Here, we identify acute cystitis as an Interleukin-1 beta (IL-1β)-driven, hyper-inflammatory condition of the infected urinary bladder and IL-1 receptor blockade as a novel therapeutic strategy. Disease severity was controlled by the mechanism of IL-1β processing and mice with intact inflammasome function developed a moderate, self-limiting form of cystitis. The most severe form of acute cystitis was detected in mice lacking the inflammasome constituents ASC or NLRP-3. IL-1β processing was hyperactive in these mice, due to a new, non-canonical mechanism involving the matrix metalloproteinase 7- (MMP-7). ASC and NLRP-3 served as transcriptional repressors of MMP7 and as a result, Mmp7 was markedly overexpressed in the bladder epithelium of Asc-/- and Nlrp3-/- mice. The resulting IL-1β hyper-activation loop included a large number of IL-1β-dependent pro-inflammatory genes and the IL-1 receptor antagonist Anakinra inhibited their expression and rescued susceptible Asc-/- mice from bladder pathology. An MMP inhibitor had a similar therapeutic effect. Finally, elevated levels of IL-1β and MMP-7 were detected in patients with acute cystitis, suggesting a potential role as biomarkers and immunotherapeutic targets. The results reproduce important aspects of human acute cystitis in the murine model and provide a comprehensive molecular framework for the pathogenesis and immunotherapy of acute cystitis, one of the most common infections in man. Trial Registration The clinical studies were approved by the Human Ethics Committee at Lund University (approval numbers LU106-02, LU236-99 and Clinical Trial Registration RTP-A2003, International Committee of Medical Journal Editors, www.clinicaltrials.gov).